The proportion of genetic similarity for liability for neuroticism in mother–child and mother–father dyads is associated with reported relationship quality - Rebecca M. Pearson; Elizabeth C. Braithwaite; Tim Cadman; Iryna Culpin; Ilaria Costantini; Miguel Cordero; Marc H. Bornstein; Deborah James; Alex S. F. Kwong; Hannah Jones; Hannah Sallis (Scientific Reports)
Abstract This study aims to explore the influence of genetic similarity for neuroticism liability in mother’s reported quality of relationship with her child and partner. Such understanding could provide insight into the role of genetic similarity in neuroticism liability in close relationships. Molecular genetic data in 4,704 mothers, partners, and children in the Avon Longitudinal Study Parents And Children (ALSPAC) study were used to derive the proportion of genetic similarity in neuroticism liability between mother and child, and mother and partner, for genetic variants associated with neuroticism. Associations between genetic similarity in neuroticism liability scores and mothers’ reported enjoyment and conflict in the parenting relationship (child ages 0–3) and her reported partner relationship were examined. For a one standard deviation (SD) increase in similarity in mother and child genetic variants associated with neuroticism, there was a 0.15SD (95%CI = 0.003 to 0.500, p = 0.046) increase in maternal reported enjoyment in their relationship. This association was greater where mother and child were both in the top quartile for high neuroticism (standardised beta = 0.29, 95%CI = 0.02 to 0.56, p = 0.034). Similar patterns of results emerged for similarity for genetic variants associated with neuroticism between mothers and partners, and the quality of the mother-partner relationship. These results highlight how phenotypic variation (i.e. the link between PGS scores and mothers reported enjoyment) linked to genetic liability in one individual may be linked with the genetic liability of those around them (i.e. the genetic liability of the infant). In other words, parenting and intimate partner relationships as perceived by the mother were explained not by one or the other’s genetic score, but by the similarity between them These exploratory findings present an intriguing mechanism by which similarity between genetic liability might be linked to family relationships.